Effects of Dietary Supplementation with Selenium-Enriched Lactobacillus plantarum on Growth, Hepatic Antioxidant Capacity, and Intestinal Microbiota of Largemouth Bass (Micropterus salmoides) - Chengxu Ruan; Junhao Tang; Xiufang Liu; Junwei Chen; Linxi Cheng; Xucong Lv (Fishes, 2026)
This study compared the effects of dietary Lactobacillus plantarum (Lpl) and selenium-enriched L. plantarum (Lpl_se) on the growth, hepatic antioxidant capacity, and intestinal microbiota of juvenile largemouth bass (initial weight 12.50 ± 0.81 g). Following a 58-day trial in an indoor rearing system, data were analyzed using one-way ANOVA followed by Tukey’s HSD test. Results showed that both Lpl and Lpl_se significantly improved growth versus the control (Weight Gain Rate: 379.82% and 387.18% vs. 326.56%; p